1996
DOI: 10.1346/ccmn.1996.0440510
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Aluminum Hydroxide Formed at the Earliest Weathering Stages of K-Feldspar

Abstract: Abstract--Weathering products formed on the surface of K-feldspar in Yakushima Island, Japan were investigated by X-ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray analysis (EDX) and X-ray photoelectron spectroscopy (XPS). XRD confirmed that the weathering products were composed mainly of gibbsite and halloysite. SEM, TEM and EDX clearly showed formation of amorphous aluminum hydroxide exhibiting 2 distinct habits: 1) curled fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Casey et al, 1989;Muir et al, 1989;Hellmann et al, 1990). Kawano and Tomita (1994) found that a tens of nm thick leached layer on albite grains hydrothermally reacted with distilled water had subsequently crystallized to Na-smectite and mica via a non-crystalline and fibrous material. Tazaki (1986) described comparable processes during natural weathering of microcline perthites from Brazil whereby 'primitive-clay precursors' were inferred to have been produced by crystallization of a leached layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Casey et al, 1989;Muir et al, 1989;Hellmann et al, 1990). Kawano and Tomita (1994) found that a tens of nm thick leached layer on albite grains hydrothermally reacted with distilled water had subsequently crystallized to Na-smectite and mica via a non-crystalline and fibrous material. Tazaki (1986) described comparable processes during natural weathering of microcline perthites from Brazil whereby 'primitive-clay precursors' were inferred to have been produced by crystallization of a leached layer.…”
Section: Discussionmentioning
confidence: 99%
“…Parham, 1969;Eggleton and Buseck, 1980;Eggleton, 1987); (3) topotactic replacement of feldspar; and (4) replacement of a 'leached layer' produced by chemical weathering of feldspar (e.g. Tazaki, 1986;Kawano and Tomita, 1994). Coatings formed by mechanisms 3 and 4 would be expected to have a low porosity and permeability and a coherent interface with the feldspar grain and so will potentially have a greater impact on weathering rates than porous aggregates of clay minerals that are likely to form by mechanisms 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…Kawano and Tomita (1996) also found gibbsite and halloysite in the early stages of weathering of K-feldspar. This study is particularly relevant to the Mt.…”
Section: Occurrence Of Clay Mineral Constituentsmentioning
confidence: 81%
“…In investigations of the products of naturally weathered potassium feldspar, Kawano and Tomita detected a surface precipitate of amorphous aluminium hydroxide with fibrous and spherical particle morphology. 16 …”
Section: Resultsmentioning
confidence: 99%